2019
DOI: 10.21273/hortsci13552-18
|View full text |Cite
|
Sign up to set email alerts
|

Screening Progenies of Mexican Race Avocado Genotypes for Resistance to Phytophthora cinnamomi Rands

Abstract: Because of the low availability of avocado rootstocks with resistance to Phytophthora cinnamomi, it is necessary to search for genotypes that offer resistance and that could be used as commercial rootstocks. The objective of this study was to select progeny from the genotypes of Mexican race avocado plants that are resistant to P. cinnamomi. Seedlings from 12 avocado genotypes were placed in containers inoculated with a mycelial suspension of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The root colonization percentages were lower for the cultivar Criollo; besides, the Kruskal Wallis test allowed to confirm differences in the response of the two cultivars evaluated, thus inferring that cultivar Criollo (Mexican race) has a greater tolerance to the pathogen. In fact, this type of cultivar has been shown to be tolerant to soil pathogens (Sánchez-González et al, 2019). In addition, according to Rincón-Hernández et al (2011), the cultivar Criollo is often used as rootstocks because it has genes for resistance to the attack of pathogens that affect the root system.…”
Section: Colonization Of the Transformed Fungus In Avocado Rootsmentioning
confidence: 99%
“…The root colonization percentages were lower for the cultivar Criollo; besides, the Kruskal Wallis test allowed to confirm differences in the response of the two cultivars evaluated, thus inferring that cultivar Criollo (Mexican race) has a greater tolerance to the pathogen. In fact, this type of cultivar has been shown to be tolerant to soil pathogens (Sánchez-González et al, 2019). In addition, according to Rincón-Hernández et al (2011), the cultivar Criollo is often used as rootstocks because it has genes for resistance to the attack of pathogens that affect the root system.…”
Section: Colonization Of the Transformed Fungus In Avocado Rootsmentioning
confidence: 99%
“…race (Bergh and Ellstrand, 1986). Previous research about the effect of the selected avocado rootstocks over crop performance has shown that trees of the same variety grafted to Mexican or Guatemalan race rootstocks differ in their susceptibility to Phytophtora cinnamomi (Smith et al, 2011;Reeksting et al, 2016;Sánchez-González et al, 2019), in their mineral nutrient uptake (Bard and Wolstenholme, 1997;Calderón-Vázquez et al, 2013), and in their response to salinity (Mickelbart and Arpaia, 2002;Raga et al, 2014). For instance, Bernstein et al (2001) demonstrated that even in selected rootstocks chosen by exhibiting excellent fruit production under elevated NaCl-condition, there is a wide range of growth sensitivities that results in growth inhibition or growth stimulation under salt-levels typically found at commercial fields.…”
Section: N R E V I E Wmentioning
confidence: 99%
“…cinnamomi (Smith et al, 2011;Reeksting et al, 2016;Sánchez-González et al, 2019), mineral nutrient uptake (Bard and Wolstenholme, 1997;Calderón-Vázquez et al, 2013), and response to salinity (Bernstein et al, 2001;Mickelbart and Arpaia, 2002;Raga et al, 2014). However, harvest/quality traits have not been explicitly considered in previous studies that aimed assessing rootstock effects on 'Hass' avocado.…”
Section: N R E V I E Wmentioning
confidence: 99%
“…This disease is also known in Mexico as avocado sadness in which the root and feeder roots shown typical root rot symptoms [ 1 , 6 ]. In Mexico, avocado root rot has been reported in the states of Queretaro, Guanajuato, Michoacan, and Puebla, with a mortality that reaches up to 100% attributed to P. cinnamomi infection [ 7 ].…”
Section: Introductionmentioning
confidence: 99%